GPU accelerated cone based shooting bouncing ray tracing - Troksa, Blake A., author; Notaros, Branislav, advisor; Pasricha, Sudeep, advisor; Chitsaz, Hamidreza, committee member (Colorado State University. Libraries, 2019)
Ray tracing can be used as an alternative method to solve complex Computational Electromagnetics (CEM) problems that would require significant time using traditional full-wave CEM solvers. Ray tracing is considered a high-frequency asymptotic solver, sacrificing accuracy for speed via approximation. Two prominent categories for ray tracing exist today: image theory techniques and ray launching techniques. Image theory involves the calculation of image points for each continuous plane within a structure. Ray launching ray tracing is comprised of spawning rays in numerous directions and tracking the intersections these rays have with the environment. While image theory ray tracing typically provides more accurate solutions compared to ray launching techniques, due to more exact computations, image theory is much slower than ray launching techniques due to exponential time complexity of the algorithm. This paper discusses a ray launching technique called shooting bouncing rays (SBR) ray tracing that applies NVIDIA graphics processing units (GPU) to achieve significant performance benefits for solving CEM problems. The GPUs are used as a tool to parallelize the core ray tracing algorithm and also to provide access to the NVIDIA OptiX ray tracing application programming interface (API) that efficiently traces rays within complex structures. The algorithm presented enables quick and efficient simulations to optimize the placement of communication nodes within complex structures. The processes and techniques used in the development of the solver and demonstrations of the validation and the application of the solver on various structures and its comparison to commercially available ray tracing software are presented.
Keywords: ray tracing; graphics processing unit; shooting bouncing rays